Una visión sucinta de la enseñanza de la medicina a lo largo de la historia : I. Desde el Antiguo Imperio Egipcio hasta el siglo XVII (2011)
ABSTRACT: In order to understand how medicine has been taught through the years, it is necessary to refer to historians who have approached the evolution of medicine. Taking them as a starting point, it is possible to describe the attitudes of doctors in their role as professors, and the ways in which students acquired knowledge at different moments throughout centuries. This article presents a succinct vision of the advances and retrogressions in medical teaching at different historical moments. It starts with the Ancient Egyptian Empire (3000-2500 b. C.) with its big legacy written on papyruses; continues with the enormous progress of Greek medicine and the obscurity of the Middle Ages, and finishes with the advances until the XVII century.